The "isohydric trap" A proposed feedback between water shortage, stomatal regulation, and nutrient acquisition drives differential growth and survival of European pines under climatic dryness - Salazar-Tortosa, Diego (Global change biology, 2018)
© 2018 John Wiley & Sons Ltd.